1984
DOI: 10.1126/science.6710145
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Mapping of the Brain During Rewarding Self-Stimulation

Abstract: Local rates of cerebral glucose utilization were measured in rats by the quantitative 2-deoxy-D-[14C]glucose autoradiographic method during electrical stimulation of the ventral tegmental area. Rats trained in intracranial self-stimulation showed a pattern of changes in forebrain metabolic activity distinctly different from the pattern seen in rats stimulated by the experimenter. These findings provide information about the distribution of local cerebral activity specific to reinforced instrumental behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1
3

Year Published

1984
1984
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(40 citation statements)
references
References 8 publications
3
33
1
3
Order By: Relevance
“…These results indicate that the overall pattern of cerebral metabolic activity associated with the behavioral pattern of self-stimulation to the VTA involves the activation of a discretely organized neural system with representation at all levels of the neuraxis. Furthermore, recent work by Porrino et al (25) indicates that this pattern of neural activity in self-stimulating animals is distinctly different from that seen when nonresponse contingent stimulation is delivered by the experimenter (at rates and current parameters comparable to those used in the present study) to VTA placements that had previously been shown to support self-stimulation at these same parameters.…”
Section: Discussioncontrasting
confidence: 71%
“…These results indicate that the overall pattern of cerebral metabolic activity associated with the behavioral pattern of self-stimulation to the VTA involves the activation of a discretely organized neural system with representation at all levels of the neuraxis. Furthermore, recent work by Porrino et al (25) indicates that this pattern of neural activity in self-stimulating animals is distinctly different from that seen when nonresponse contingent stimulation is delivered by the experimenter (at rates and current parameters comparable to those used in the present study) to VTA placements that had previously been shown to support self-stimulation at these same parameters.…”
Section: Discussioncontrasting
confidence: 71%
“…Application of this strategy is already obvious in studies which have successfully identified the brain regions that get activated following SS of MFB sites. In these studies the 2-deoxyglucose autoradiography, 13,16,34,35 or the cytochrome oxidase staining 3 were used. In both techniques the neuronal activation is quantitatively determined through optical density measurements.…”
mentioning
confidence: 99%
“…The pattern of regional metabolic activation of the rat brain after rewarding electrical self-stimulation of the VTA or cocaine is quite different from the pattern seen after stimulation of the same area by the experimenter (Howell, Votaw, Goodman, & Lindsey, 2010;Porrino et al, 1984). It is widely recognized that hospitalized patients to whom high doses of opioid drugs are administered by treatment personnel for relief of severe pain frequently develop tolerance and physical dependence, yet they seldom become compulsive drug seekers and users (O'Brien, 2001).…”
Section: Evidence That Does Not Support An Exclusively Neurobiologicamentioning
confidence: 85%